“Deserdados da sorte” – mapeamento de pesquisas sobre “menores desvalidos” e educação assistencialista na Amazônia brasileira: “Disinhereted of luck” – research mapping on “disabled minors” and care education in the Brazilian Amazon - Reis de Sousa, Graciene; dos santos, jocyleia (Revista Cocar, 2022)
Esta pesquisa teve como finalidade mapear teses e dissertações dos Programas de Pós-Graduação em Educação nas Universidades que se encontram na Amazônia Brasileira, sobre a história das instituições educativas pautadas no assistencialismo de “menores desvalidos” na Região Norte do Brasil. Como metodologia utilizou-se o “estado de conhecimento” amparado nas autoras MOROSINI e FERNANDES (2014). O levantamento de dados foi realizado na base da Capes, com recorte temporal dos últimos cinco anos (2016-2020). A base teórica fundante para a construção e complementação do estado da arte, teve como referência: ALVES (2018); COLARES (2002 e 2011); RIZZINI (2006) e SCHUELER (2009). Constata-se que a maioria dos trabalhos, no campo da história da educação, com ênfase na infância desvalida e em instituições educativas de cunho assistencialista são defendidas nos programas de pós-graduação do Sul e Sudeste do país, havendo, portanto, necessidade de ampliação de estudos dessa natureza na região Norte do Brasil. Palavras-chave Estado do conhecimento, Educação na Amazônia, Menores desvalidos. Abstract This research aimed to map theses and dissertations from the Graduate Programs in Education in Universities located in the Brazilian Amazon, on the history of educational institutions based on the assistance of “underprivileged minors” in the Northern Region of Brazil. As a methodology, the “state of knowledge” was used, supported by the authors MOROSINI and FERNANDES (2014). Data collection was carried out based on Capes, with a time frame of the last five years (2016-2020). The theoretical foundation for the construction and complementation of the state of the art, had as reference: ALVES (2018); NECKLACES (2002 and 2011); RIZZINI (2006) and SCHUELER (2009). It appears that most works in the field of the history of education, with an emphasis on underprivileged childhood and on educational institutions of a welfarist nature, are defended in postgraduate programs in the South and Southeast of the country, and there is, therefore, a need to expand of studies of this nature in the North region of Brazil. Key words: State of knowledge, Education in the Amazon, Underprivileged Minors, Assistance.